Electrolyte, battery, energy storage device and energy storage system

By using an electrolyte containing non-polar solvent, sodium difluorophosphate and sodium difluorosulfonimide in sodium ion batteries, the problem of poor capacity attenuation and circulation performance of sodium ion batteries at high and low temperatures is solved, and the battery's high circulation capacity retention rate and extended service life are achieved in a wide temperature range.

CN119601771APending Publication Date: 2025-03-11XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411726119.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The capacity attenuation of existing sodium ion batteries at high and low temperatures is severe, and the circulation performance is poor.

Method used

An electrolyte is used, which comprises a non-polar solvent, sodium difluorophosphate and sodium difluorosulfonimide. Non-polar solvents broaden the operating temperature range of the battery, and sodium difluorosulfonimide and sodium difluorosulfonimide reduce the impedance growth during the battery cycle, improving the rate performance, high-temperature circulation performance and low-temperature circulation performance of the battery.

Benefits of technology

Through the use of this electrolyte, the battery has a high circulation capacity retention rate in a wide temperature range of -40°C to 80°C, which extends the service life of the battery and significantly improves the circulation performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601771A_ABST
    Figure CN119601771A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte, a battery, an energy storage device and an energy storage system. The electrolyte comprises an electrolyte salt, a first organic solvent, a second organic solvent and a first additive, the first organic solvent is a polar solvent, the second organic solvent is a non-polar solvent, and the first additive comprises sodium difluorophosphate and sodium bis (fluorosulfonyl) imide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage, and specifically to an electrolyte, a battery, an energy storage device and an energy storage system. Background Art

[0002] With the increasing popularity of electric vehicles, the global demand for lithium-ion batteries has surged, raising concerns about the sustainable supply of lithium due to its limited supply, uneven geographical distribution and high price. Sodium-ion batteries have become a promising alternative due to their abundant and low-cost sodium resources. However, existing sodium-ion batteries suffer from severe capacity decay at high and low temperatures, and their cycle performance is still poor. Summary of the invention

[0003] The embodiment of the present application provides an electrolyte, which, when applied to a battery, enables the battery to have a wider operating temperature, and has a higher cycle capacity retention rate within the wider operating temperature range.

[0004] In a first aspect, an embodiment of the present application provides an electrolyte, comprising an electrolyte salt, a first organic solvent, a second organic solvent, and a first additive, wherein the first organic solvent is a polar solvent, the second organic solvent is a non-polar solvent, and the first additive comprises sodium difluorophosphate and sodium bis(fluorosulfonyl)imide.

[0005] In a second aspect, an embodiment of the present application further provides a battery, comprising:

[0006] The electrolyte described in the embodiment of the present application;

[0007] A positive electrode sheet, the positive electrode sheet is immersed in the electrolyte;

[0008] a diaphragm, located on one side of the positive electrode plate and immersed in the electrolyte, and

[0009] A negative electrode plate is disposed on a side of the diaphragm away from the positive electrode plate and immersed in the electrolyte.

[0010] In a third aspect, an embodiment of the present application further provides an energy storage device, comprising:

[0011] The housing; and

[0012] A plurality of batteries according to the embodiments of the present application are contained in the box.

[0013] In a fourth aspect, an embodiment of the present application further provides an energy storage system, comprising: an electric energy conversion device and the energy storage device described in the embodiment of the present application, the electric energy conversion device being electrically connected to the energy storage device, the electric energy conversion device being used to convert other forms of energy into electric energy, and the energy storage device being used to store the electric energy.

[0014] The electrolyte of the present application includes a second organic solvent, which is a non-polar solvent. The non-polar solvent has a lower melting point and a smaller viscosity, which can greatly broaden the operating temperature range of the sodium ion battery, improve the sodium ion transfer rate, and better inhibit the side reactions at the positive electrode plate / electrolyte interface and the negative electrode plate / electrolyte interface. Sodium difluorophosphate and sodium bis(fluorosulfonyl)imide can effectively reduce the impedance growth during the battery cycle, and form an interface film rich in inorganic components on the surface of the positive electrode plate and the negative electrode plate, which can effectively improve the rate performance, high temperature cycle performance and low temperature cycle performance of the battery. The competitive coordination between the solvent and the anion (such as difluorophosphate and bis(fluorosulfonyl)imide) is a key factor in determining the composition and structure of the solid electrolyte interface membrane (Solid Electrolyte Interface membrane, referred to as SEI membrane). In addition, the non-polar solvent can reduce the solvation capacity of the electrolyte, so that the anion content of the solvated inner layer gradually increases, and the interface chemistry gradually transitions from solvent-dominated to anion-dominated. Furthermore, non-polar solvents do not participate in coordination. The anion radius of sodium difluorophosphate and sodium bis(fluorosulfonyl)imide is large, easy to dissociate, and preferentially enter the solvation inner layer to form ion pairs or aggregates. This solvation structure leads to anion-derived solid electrolyte interface film, so that the battery can achieve fast and long-term cycling. Furthermore, sodium difluorophosphate, due to its high reduction potential, first participates in the film-forming reaction of the negative electrode sheet, forming an inorganic solid electrolyte interface film rich in sodium fluoride on the surface of the negative electrode active layer; the introduction of sodium bis(fluorosulfonyl)imide increases the organic content in the SEI film of the negative electrode sheet, and sodium fluoride has a strong adhesion to organic matter. The two together form a stable and strong organic-inorganic solid electrolyte interface film on the surface of the negative electrode active layer (hard carbon), thereby improving the interface stability between the negative electrode sheet and the electrolyte and inhibiting the consumption of the electrolyte during the cycle. Furthermore, difluorophosphate can inhibit the hydrolysis of sodium hexafluorophosphate and the generation of hydrofluoric acid, and bisfluorosulfonyl imide can effectively passivate metallic sodium and reduce the generation of gas during low-temperature cycles. In summary, the electrolyte of the embodiment of the present application includes a non-polar solvent, sodium difluorophosphate and sodium bisfluorosulfonyl imide. The synergistic effect of non-polar solvents, sodium difluorophosphate and sodium bisfluorosulfonyl imide improves the conductivity of the electrolyte, reduces the impedance of the battery, improves the stability of the positive electrode / electrolyte interface and the negative electrode / electrolyte interface, inhibits the side reactions of the battery during high-temperature cycles and low-temperature cycles, reduces the consumption of solvents and sodium salts in the electrolyte, extends the service life of the battery, and effectively broadens the operating temperature of the electrolyte. It can also be understood that the synergistic combination of non-polar solvents with sodium difluorophosphate and sodium bis(fluorosulfonyl)imide can regulate the sodium ion solvation structure of the battery, greatly reducing the side reactions at the interface of the positive electrode sheet / electrolyte and the interface of the negative electrode sheet / electrolyte, while reducing the desolvation energy barrier of sodium ions at low temperatures, thereby achieving the battery's ability to operate at a wide temperature range of -40°C to 80°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0016] Figure 1 It is a structural block diagram of an energy storage system according to an embodiment of the present application.

[0017] Figure 2 This is an application scenario diagram of an energy storage system according to an embodiment of the present application.

[0018] Figure 3 It is a schematic structural diagram of an energy storage device according to an embodiment of the present application.

[0019] Figure 4 It is a schematic diagram of the structure of a battery according to an embodiment of the present application.

[0020] Figure 5 The battery of one embodiment of the present application is Figure 4 Schematic diagram of the cross-sectional structure in the AA direction.

[0021] Figure 6 It is a schematic diagram of the cross-sectional structure of a positive electrode plate according to an embodiment of the present application.

[0022] Figure 7 It is a schematic diagram of the cross-sectional structure of a negative electrode plate according to an embodiment of the present application.

[0023] Description of reference numerals:

[0024] 100 -battery, 110 -positive electrode plate, 111 -positive current collector, 112 -positive electrode active layer, 120 -diaphragm, 130 -negative electrode plate, 131 -negative current collector, 132 -negative electrode active layer, 140 -housing, 150 -end cover assembly, 141 -receiving chamber, 200 -energy storage device, 210 -casing, 300 -energy storage system, 310 -electric energy conversion device. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0026] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.

[0027] The technical solutions in the embodiments of the present application will be described below in conjunction with the accompanying drawings.

[0028] It should be noted that, for the convenience of explanation, in the embodiments of the present application, the same figure marks represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments.

[0029] At present, the generation of green electricity generally relies on photovoltaics, wind power, and hydropower, etc. However, wind and solar energy generally have problems of strong intermittency and large volatility, which will cause instability in the power grid, insufficient electricity during peak hours, and too much electricity during valley hours. Unstable voltage will also cause damage to electricity. Therefore, insufficient electricity demand or insufficient grid acceptance capacity may cause the problem of "abandoning wind and solar power". To solve these problems, we must rely on energy storage. That is, converting electrical energy into other forms of energy through physical or chemical means and storing it, and converting energy into electrical energy and releasing it when needed. In simple terms, energy storage is like a large "power bank". When photovoltaic and wind energy are sufficient, electrical energy is stored and the stored electricity is released when needed.

[0030] The current energy storage (i.e., energy storage) application scenarios are relatively broad, including power generation side energy storage, grid side energy storage, and power consumption side energy storage. The following uses power generation side energy storage as an example to describe the energy storage system of the embodiment of the present application in detail, which should not be understood as a limitation on the energy storage system of the embodiment of the present application.

[0031] See also Figure 1 and Figure 2 The embodiment of the present application also provides an energy storage system 300, which includes: an electric energy conversion device 310 and the energy storage device 200 described in the embodiment of the present application, the electric energy conversion device 310 is electrically connected to the energy storage device 200, the electric energy conversion device 310 is used to convert other forms of energy into electric energy, and the energy storage device 200 is used to store the electric energy.

[0032] Optionally, the electric energy conversion device 310 can convert at least one other form of energy such as solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.

[0033] Optionally, the number of the electric energy conversion devices 310 may be one or more. When there are multiple electric energy conversion devices 310, the multiple electric energy conversion devices 310 may be connected in series, in parallel, or in mixed connection, which is not specifically limited in the present application.

[0034] Optionally, the electric energy conversion device 310 may be, but is not limited to, at least one of a photovoltaic panel, a wind power generation device, a hydropower generation device, and the like.

[0035] Optionally, the number of the energy storage devices 200 may be one or more. When the number of the energy storage devices 200 is multiple, the multiple energy storage devices 200 are connected in series or in parallel, which is not specifically limited in the present application.

[0036] When working, the power conversion device 310 is used to convert other forms of energy into electrical energy and store it in the energy storage device 200. The electrical energy stored in the energy storage device 200 can be supplied to electrical loads such as street lamps and household appliances for use when the electricity price is at a peak, or to supply power when the power grid is out of power. The electrical energy generated by the power conversion device 310 can also be supplied to the power grid through high-voltage cables to alleviate the power supply pressure of the power grid during peak hours.

[0037] See also Figure 3 The embodiment of the present application further provides an energy storage device 200 , which includes a box 210 and a plurality of batteries 100 , wherein the plurality of batteries 100 are stacked and accommodated in the box 210 .

[0038] The term "plurality" means greater than or equal to two.

[0039] It can be understood that the multiple batteries 100 of the energy storage device 200 can be connected in parallel with each other; or in series with each other; or partially in parallel and partially in series (in other words, mixed connection). This application does not make any specific restrictions on the connection method of multiple batteries 100 of the same energy storage device 200.

[0040] Optionally, the energy storage device may be at least one of a small energy storage box, a large energy storage cabinet, an energy storage module, etc. The present application does not specifically limit the form of the energy storage device. The form of the energy storage device of the present application is only one of its many forms and should not be understood as a limitation on the energy storage device of the present application.

[0041] It can be understood that the box body 210 has a receiving cavity, and multiple batteries 100 are received in the receiving cavity. In some embodiments, each receiving cavity receives one battery 100. In other embodiments, each receiving cavity receives multiple batteries 100.

[0042] With the increasing popularity of electric vehicles, the global demand for lithium-ion batteries has surged, raising concerns about the sustainable supply of lithium due to its limited supply, uneven geographical distribution and high price. Sodium-ion batteries have become a promising alternative due to their abundant and low-cost sodium resources. However, existing sodium-ion batteries suffer from severe capacity decay at high and low temperatures, and their cycle performance is still poor.

[0043] See also Figure 4 and Figure 5 The embodiment of the present application provides a battery 100, which includes an electrolyte, a positive electrode plate 110, a separator 120 and a negative electrode plate 130, wherein the separator 120 is located on one side of the positive electrode plate 110; the negative electrode plate 130 is arranged on the side of the separator 120 away from the positive electrode plate 110.

[0044] The battery 100 in the embodiment of the present application may be, but is not limited to, a sodium ion battery.

[0045] It should be noted that the positive electrode sheet 110 and the negative electrode sheet 130 are at least partially immersed in the electrolyte.

[0046] It can be understood that the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are stacked in sequence to form an electrode assembly. The electrode assembly can be, but is not limited to, a winding structure, a laminated structure, etc., which is not specifically limited in the present application.

[0047] It should be noted that the positive electrode sheet 110 and the negative electrode sheet 130 may be collectively referred to as electrode sheets. In other words, the electrode sheets include the positive electrode sheet 110 and the negative electrode sheet 130 .

[0048] See also Figure 6 Optionally, the positive electrode sheet 110 includes a positive current collector 111 and a positive active layer 112, and the positive active layer 112 is disposed on the surface of the positive current collector 111. It can be understood that the positive active layer 112 can cover one surface or two opposite surfaces of the positive current collector 111.

[0049] Optionally, the positive electrode current collector 111 may be, but is not limited to, an aluminum sheet.

[0050] Optionally, the positive electrode active layer 112 includes a positive electrode active material, a positive electrode conductor, a positive electrode binder and a positive electrode thickener.

[0051] Optionally, the positive electrode active material may be, but is not limited to, sodium iron phosphate.

[0052] Optionally, the positive electrode conductive agent may be, but is not limited to, at least one of conductive carbon black, acetylene black, carbon nanotubes, carbon fibers, graphene, and the like.

[0053] Optionally, the positive electrode binder may be, but is not limited to, at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), polyhexafluoropropylene, and styrene butadiene rubber (SBR).

[0054] Optionally, in the positive electrode active layer 112, the mass fraction of the positive electrode binder ranges from 2wt% to 4wt%. Specifically, in the positive electrode active layer 112, the mass fraction of the positive electrode binder may be, but is not limited to, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, etc. If the mass fraction of the positive electrode binder is too small, the positive electrode active layer 112 is prone to pulverization or slag; if the mass fraction of the positive electrode binder is too large, the energy density of the positive electrode sheet 110 is reduced.

[0055] Optionally, the positive electrode thickener may be, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC for short), polyacrylamide (PAM) and polymethacrylate (PMA).

[0056] Optionally, the diaphragm 120 may be, but is not limited to, at least one of a polypropylene film (PP film for short), a polyethylene film (PE film for short), a ceramic diaphragm 120 , and the like.

[0057] Optionally, the thickness of the diaphragm 120 is 14 μm to 18 μm. Specifically, the thickness of the diaphragm 120 may be, but is not limited to, 14 μm, 14.5 μm, 15 μm, 15.5 μm, 16 μm, 16.5 μm, 17 μm, 17.5 μm, 18 μm, etc.

[0058] See also Figure 7 Optionally, the negative electrode sheet 130 includes a negative electrode current collector 131 and a negative electrode active layer 132, and the negative electrode active layer 132 is disposed on the surface of the negative electrode current collector 131. It can be understood that the negative electrode active layer 132 can cover one surface or two opposite surfaces of the negative electrode current collector 131.

[0059] Optionally, the negative electrode current collector 131 may be, but is not limited to, a copper sheet.

[0060] Optionally, the negative electrode active layer 132 includes a negative electrode active material, a negative electrode conductor, a negative electrode binder and a negative electrode thickener.

[0061] Alternatively, the negative electrode active material may be, but is not limited to, at least one of graphite, hard carbon, and the like.

[0062] Optionally, the negative electrode conductive agent may be, but is not limited to, at least one of conductive carbon black (SP for short), acetylene black, carbon nanotubes, carbon fibers, graphene, and the like.

[0063] Optionally, the negative electrode binder may be, but is not limited to, at least one of polyvinylidene fluoride, polyamide, polyacrylonitrile, polyacrylate, polyvinyl ether, polymethyl methacrylate, polyhexafluoropropylene, styrene-butadiene rubber, and the like.

[0064] Optionally, in the negative electrode active layer 132, the mass fraction of the negative electrode binder ranges from 2wt% to 4wt%. Specifically, in the negative electrode active layer 132, the mass fraction of the negative electrode binder may be, but is not limited to, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, etc. If the mass fraction of the negative electrode binder is too small, the negative electrode active layer 132 is prone to pulverization or slag; if the mass fraction of the negative electrode binder is too large, the energy density of the negative electrode plate 130 is reduced.

[0065] Optionally, the negative electrode thickener may be, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC for short), polyacrylamide (PAM) and polymethacrylate (PMA).

[0066] Please see again Figure 4 and Figure 5 Optionally, the battery 100 further includes a shell 140 and an end cover assembly 150 , wherein the shell 140 and the end cover assembly 150 enclose a receiving cavity 141 , and the receiving cavity 141 is used to receive the electrolyte, the positive electrode plate 110 , the diaphragm 120 and the negative electrode plate 130 .

[0067] An embodiment of the present application also provides an electrolyte, which includes an electrolyte salt, a first organic solvent, a second organic solvent and a first additive, wherein the first organic solvent is a polar solvent, the second organic solvent is a non-polar solvent, and the first additive includes sodium difluorophosphate and sodium bis(fluorosulfonyl)imide.

[0068] It can be understood that the electrolyte in the embodiment of the present application is a non-aqueous electrolyte.

[0069] The electrolyte of the present application includes a second organic solvent, which is a non-polar solvent. The non-polar solvent has a lower melting point and a smaller viscosity, which can greatly broaden the operating temperature range of the sodium ion battery 100, improve the sodium ion transmission rate, and better inhibit the side reactions at the positive electrode plate 110 / electrolyte interface and the negative electrode plate 130 / electrolyte interface. Sodium difluorophosphate and sodium bis(fluorosulfonyl)imide can effectively reduce the impedance growth of the battery 100 during the cycle process, and form an interface film rich in inorganic components on the surface of the positive electrode plate 110 and the negative electrode plate 130, which can effectively improve the rate performance, high temperature cycle performance and low temperature cycle performance of the battery 100. The competitive coordination between the solvent and the anion (such as difluorophosphate and bis(fluorosulfonyl)imide) is a key factor in determining the composition and structure of the solid electrolyte interface membrane (SEI membrane). In addition, non-polar solvents can reduce the solvation capacity of the electrolyte, so that the anion content of the solvation inner layer gradually increases, and the interface chemistry gradually transitions from solvent-dominated to anion-dominated. Furthermore, non-polar solvents do not participate in coordination, and the anions of sodium difluorophosphate and sodium bis(fluorosulfonyl)imide have large radii and are easy to dissociate, preferentially entering the solvation inner layer to form ion pairs or aggregates. This solvation structure leads to an anion-derived solid electrolyte interface film, so that the battery 100 can achieve fast and long-term cycling. Furthermore, due to its high reduction potential, sodium difluorophosphate first participates in the film-forming reaction of the negative electrode plate 130, and forms an inorganic solid electrolyte interface film rich in sodium fluoride on the surface of the negative active layer 132; the introduction of sodium bis(fluorosulfonyl)imide increases the organic content in the SEI film of the negative electrode plate 130, and sodium fluoride has a strong adhesion to organic matter. The two together form a stable and strong organic-inorganic solid electrolyte interface film on the surface of the negative active layer 132 (hard carbon), thereby improving the interface stability between the negative electrode plate 130 and the electrolyte, and inhibiting the consumption of the electrolyte during the cycle. Furthermore, difluorophosphate can inhibit the hydrolysis of sodium hexafluorophosphate and the generation of hydrofluoric acid, and bis(fluorosulfonyl)imide can effectively passivate metallic sodium and reduce the generation of gas during low-temperature cycles. In summary, the electrolyte of the embodiment of the present application includes a non-polar solvent, sodium difluorophosphate and sodium bis(fluorosulfonyl)imide. The synergistic effect of non-polar solvents, sodium difluorophosphate and sodium bis(fluorosulfonyl)imide improves the conductivity of the electrolyte, reduces the impedance of the battery 100, improves the stability of the positive electrode plate 110 / electrolyte interface and the negative electrode plate 130 / electrolyte interface, inhibits the side reactions of the battery 100 during high-temperature and low-temperature cycles, reduces the consumption of solvents and sodium salts in the electrolyte, extends the service life of the battery 100, and effectively broadens the operating temperature of the electrolyte.It can also be understood that the non-polar solvent cooperates with sodium difluorophosphate and sodium bis(fluorosulfonyl)imide to regulate the sodium ion solvation structure of the battery 100, greatly reducing the side reactions at the interface of the positive electrode plate 110 / electrolyte and the interface of the negative electrode plate 130 / electrolyte, while reducing the desolvation energy barrier of sodium ions at low temperatures, thereby achieving the working ability of the battery 100 at a wide temperature range of -40°C to 80°C.

[0070] In some embodiments, the mass ratio a1 / a2 of the first organic solvent to the second organic solvent is in the range of 0.25≤a1 / a2≤3.

[0071] Specifically, the mass ratio a1 / a2 of the first organic solvent to the second organic solvent may be, but is not limited to, 0.25, 0.3, 0.4, 0.5, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, etc.

[0072] In this embodiment, if the mass ratio a1 / a2 of the first organic solvent to the second organic solvent is too low, the mass fraction of the non-polar solvent in the electrolyte is too large, the compatibility between the first organic solvent and the second organic solvent deteriorates, and the degree of inhomogeneity of the electrolyte increases, which may affect the charge and discharge performance of the battery 100; if the mass ratio a1 / a2 of the first organic solvent to the second organic solvent is too high, the content of the first organic solvent in the electrolyte is too large, the viscosity of the electrolyte is too low, and the low-temperature cycle performance of the battery 100 is reduced.

[0073] In some embodiments, the mass fraction a1 of the first organic solvent in the electrolyte is in the range of 20wt%≤a1≤70wt%.

[0074] Optionally, the mass fraction a1 of the polar solvent in the electrolyte is in the range of 20wt%≤a1≤70wt%.

[0075] Specifically, the mass fraction a1 of the first organic solvent in the electrolyte can be but is not limited to 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt% and the like.

[0076] In this embodiment, if the mass fraction a1 of the first organic solvent in the electrolyte is too small, the electrolyte's ability to dissolve sodium salts is reduced, the viscosity of the electrolyte is increased, and the low-temperature cycle performance of the battery 100 is reduced; if the mass fraction a1 of the first organic solvent in the electrolyte is too large, the solvent molecules first enter the solvation shell during the solvation process of the electrolyte to form a loosely structured solid electrolyte interface film, which accelerates the consumption of the electrolyte during the cycle and reduces the cycle performance of the battery 100.

[0077] In some embodiments, the electrolyte further includes a second organic solvent, the second organic solvent is a carbonate, and in the electrolyte, the mass fraction a2 of the second organic solvent is in the range of 20wt%≤a2≤65wt%.

[0078] Optionally, in the electrolyte, the mass fraction a2 of the non-polar solvent is in the range of 20wt%≤a2≤65wt%.

[0079] Specifically, the mass fraction a2 of the second organic solvent in the electrolyte can be but is not limited to 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt% and the like.

[0080] In this embodiment, if the mass fraction a2 of the non-polar solvent in the electrolyte is too low, the viscosity of the electrolyte increases, and it is difficult to improve the low-temperature cycle performance of the battery 100, that is, the low-temperature cycle performance of the battery 100 is reduced; if the mass fraction a2 of the non-polar solvent in the electrolyte is too high, the compatibility between the first organic solvent and the second organic solvent is limited, which easily causes stratification of the electrolyte, and may affect the charge and discharge performance of the battery 100.

[0081] Furthermore, the mass fraction a2 of the second organic solvent in the electrolyte is in the range of 45wt%≤a2≤60wt%. When the mass fraction of the second organic solvent in the electrolyte is in this range, the battery 100 can have better low-temperature cycle performance and the electrolyte is not easily stratified, and the battery 100 has better discharge performance.

[0082] In some embodiments, the first organic solvent includes alkanes. It is understood that the solvation shell refers to the solvent molecule adsorption layer formed by the solvent molecules in the battery 100 on the surface of the positive electrode plate 110 or the surface of the negative electrode plate 130. Among them, the layer of solvent molecules adjacent to the surface of the positive electrode plate 110 or the surface of the negative electrode plate 130 is the first solvation shell, and there is also a second solvation shell outside the first solvation shell. In the solvation shell, it is difficult for the sodium ions in the non-aqueous electrolyte to separate from the solvent after combining with the solvent molecules. When alkanes are used in the embodiments of the present application, their strong desolvation effect is conducive to the release of sodium ions from the solvent, while allowing more anions to enter the first solvation shell. In this way, more anions participate in the formation of the SEI interface film, which can passivate metallic sodium and inhibit the low-temperature cycle gas production of the battery 100 on the one hand, and reduce the consumption of solvents and sodium salts on the other hand, and improve the cycle capacity retention rate of the battery 100.

[0083] Optionally, the alkane includes at least one of n-hexane, octane and methylcyclopentane. These solvents have a lower melting point and viscosity, and have a weaker solvation effect, so that the anions in the electrolyte can more fully participate in the solvation inner layer, inhibiting further decomposition of the solvent and the sodium salt.

[0084] In one specific embodiment, the non-polar alkane is methylcyclopentane. Methylcyclopentane has a higher lowest unoccupied molecular orbital (LUMO) energy level and a lower highest occupied molecular orbital (HOMO) energy level, which makes it exhibit better redox stability.

[0085] Optionally, the second organic solvent comprises a carbonate.

[0086] Optionally, the second organic solvent includes at least one of a cyclic carbonate and a chain carbonate. Cyclic carbonate has a high dielectric constant and high ionic conductivity, and can form a stable SEI film on the surface of the negative electrode plate 130, but its viscosity is relatively large. Chain carbonate has a lower viscosity than cyclic carbonate, better electrochemical stability, and can improve the low-temperature performance of the electrolyte. Therefore, when a mixed solvent of cyclic carbonate and chain carbonate is used, the electrolyte can have a more suitable viscosity and low-temperature stability, and the battery 100 using the electrolyte can be better film-formed.

[0087] Optionally, the cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC for short), propylene carbonate (PC for short), etc. The dielectric constant of ethylene carbonate is much greater than that of propylene carbonate, and ethylene carbonate can better promote the formation of SEI film.

[0088] Optionally, the linear carbonate may include but is not limited to at least one of dimethyl carbonate (DMC for short), diethyl carbonate (DEC for short), ethyl methyl carbonate (EMC for short), and the like.

[0089] In some embodiments, in the electrolyte, the mass fraction b of the first additive is in the range of 1.2wt%≤b≤5.5wt%.

[0090] It can be understood that the sum of the mass fractions of sodium difluorophosphate and sodium bis(fluorosulfonyl)imide in the electrolyte is in the range of 1.2 wt % to 5.5 wt %.

[0091] Specifically, the mass fraction b of the first additive in the electrolyte can be but is not limited to 1.2wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.2wt%, 5.5wt%, etc.

[0092] In this embodiment, if the mass fraction b of the first additive in the first electrolyte is too low, the solvent molecules first enter the solvation shell during the solvation process of the electrolyte, forming a loosely structured solid electrolyte interface film, accelerating the consumption of the electrolyte during the cycle, reducing the cycle performance of the battery 100, and not significantly improving the electrolyte solvation structure and the high-temperature cycle performance of the battery 100. If the mass fraction b of the first additive in the first electrolyte is too large, the electrolyte's solubility for sodium salts is reduced, the viscosity of the electrolyte is increased, and the low-temperature cycle performance of the battery 100 is reduced.

[0093] Furthermore, in the electrolyte, the mass fraction b of the first additive is in the range of 3.2wt%≤b≤5.5wt%. In this way, the battery 100 can have better low-temperature cycle performance and better high-temperature cycle performance.

[0094] In some embodiments, in the electrolyte, the mass ratio b1 / b2 of the mass fraction b1 of the sodium difluorophosphate to the mass fraction b2 of the sodium bis(fluorosulfonyl)imide is in the range of 0.075≤b1 / b2≤0.35.

[0095] Specifically, in the electrolyte, the mass ratio b1 / b2 of the mass fraction b1 of the sodium difluorophosphate to the mass fraction b2 of the sodium bis(fluorosulfonyl)imide may be, but is not limited to, 0.075, 0.08, 0.10, 0.12, 0.14, 0.16, 0.18, 0.20, 0.22, 0.24, 0.25, 0.28, 0.3, 0.32, 0.35, etc.

[0096] In this embodiment, if the mass ratio b1 / b2 of the mass fraction b1 of the sodium difluorophosphate to the mass fraction b2 of the sodium bis(fluorosulfonyl)imide in the electrolyte is too small, the mass fraction of the sodium bis(fluorosulfonyl)imide in the electrolyte is too large, the viscosity of the electrolyte increases, and the low-temperature performance of the battery 100 deteriorates; if the mass ratio b1 / b2 of the mass fraction b1 of the sodium difluorophosphate to the mass fraction b2 of the sodium bis(fluorosulfonyl)imide in the electrolyte is too large, the mass fraction of the sodium difluorophosphate in the electrolyte is too large, and the solubility limit in the electrolyte is exceeded.

[0097] In some embodiments, in the electrolyte, the mass fraction b1 of the sodium difluorophosphate is in the range of 0.2wt%≤b1≤0.8wt%.

[0098] Specifically, the mass fraction b1 of sodium difluorophosphate in the electrolyte may be, but is not limited to, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, etc.

[0099] In this embodiment, if the mass fraction b1 of sodium difluorophosphate in the electrolyte is too low, it will be disadvantageous to improve the high temperature cycle performance of the battery 100 to a limited extent; if the mass fraction b1 of sodium difluorophosphate in the electrolyte is too high, it will exceed the upper limit of solubility in the electrolyte.

[0100] In some embodiments, in the electrolyte, the mass fraction b2 of the sodium bis(fluorosulfonyl)imide is in the range of 1wt%≤b2≤5wt%.

[0101] Specifically, in the electrolyte, the mass fraction b2 of the sodium bis(fluorosulfonyl)imide may be, but is not limited to, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, etc.

[0102] In this embodiment, in the electrolyte, the mass fraction b2 of the sodium bis(fluorosulfonyl)imide is too low, which reduces the improvement in suppressing the side reactions of the battery 100 at high temperatures, and is not conducive to improving the high-temperature cycle performance of the battery 100; if the mass fraction of the sodium bis(fluorosulfonyl)imide is too large, the viscosity of the electrolyte increases, and the low-temperature performance of the battery 100 deteriorates.

[0103] In some embodiments, the electrolyte further includes a second additive, and the second additive includes at least one of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, 1,3-propylene sultone (Prop-1-ene-1,3-sultone, PST), vinyl sulfate (1,3,2-Dioxathiolane 2,2-dioxide, DTD), and vinyl sulfite.

[0104] In this embodiment, by adding the second additive, the second additive acts synergistically with sodium difluorophosphate and sodium bis(fluorosulfonyl)imide. The second additive can assist the first additive, promote better film formation of the SEI film, improve the stability of the SEI film, and thus improve the cycle performance of the battery 100.

[0105] Optionally, in the electrolyte, the mass fraction of the second additive ranges from 0.01 wt % to 2 wt %.

[0106] Specifically, in the electrolyte, the mass fraction of the second additive may be, but is not limited to, 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, etc.

[0107] In this embodiment, if the mass fraction of the second additive is too low, it will not provide enough inorganic elements to form an inorganic-rich solid electrolyte interface film during the formation process; if the mass fraction of the second additive is too high, the impedance of the battery 100 will increase and the rate performance of the battery 100 will be reduced.

[0108] Furthermore, in the electrolyte, the mass fraction of the second additive is in the range of 1 wt % to 2 wt %, so that the battery 100 can have a better cycle capacity retention rate and better rate performance.

[0109] Optionally, the electrolyte salt may be, but is not limited to, a sodium salt. Optionally, the sodium salt may include, but is not limited to, sodium hexafluorophosphate.

[0110] Optionally, in the electrolyte, the molar concentration of the sodium salt ranges from 0.5 mol / L to 1.2 mol / L. Specifically, in the electrolyte, the molar concentration of the sodium salt may be, but is not limited to, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, etc. If the molar concentration of the sodium salt in the electrolyte is too low, the conductivity of the electrolyte is reduced, thereby reducing the kinetic performance of the battery 100; if the molar concentration of the sodium salt in the electrolyte is too high, a portion of the electrolyte salt is likely to remain undissociated, and the viscosity of the electrolyte is increased, which in turn reduces the conductivity of the electrolyte and also reduces the kinetic performance of the battery 100. When the molar concentration of the sodium salt in the electrolyte is in the range of 0.5 mol / L to 1.2 mol / L, the electrolyte can have a higher conductivity, so that the battery 100 has better kinetic performance.

[0111] In some embodiments, the battery 100 satisfies at least one of the following conditions:

[0112] The discharge capacity retention rate of the battery 100 at -40°C is greater than or equal to 75.4%;

[0113] The capacity retention rate of the battery 100 after 200 cycles at -20°C is greater than or equal to 80.3%;

[0114] The capacity retention rate of the battery 100 at 25° C. and 5C discharge rate is greater than or equal to 92.7%;

[0115] The capacity retention rate of the battery 100 after 3000 cycles at 25° C. is greater than or equal to 93.4%;

[0116] The capacity retention rate of the battery 100 stored at 45° C. for 30 days is greater than or equal to 90.8%; and

[0117] The capacity retention rate of the battery 100 after 500 cycles at 80° C. is greater than or equal to 82%.

[0118] Specifically, the discharge capacity retention rate of the battery 100 at -40°C may be, but is not limited to, greater than or equal to 75.4%, greater than or equal to 78%, greater than or equal to 80%, greater than or equal to 83%, greater than or equal to 85%, greater than or equal to 88%, greater than or equal to 90%, etc.

[0119] Specifically, the capacity retention rate of the battery 100 after 200 cycles at -20°C may be, but is not limited to, greater than or equal to 80.3%, greater than or equal to 83%, greater than or equal to 85%, greater than or equal to 88%, greater than or equal to 90%, greater than or equal to 93%, greater than or equal to 95%, etc.

[0120] Specifically, the capacity retention rate of the battery 100 at 25° C. and discharged at a 5C rate may be, but is not limited to, greater than or equal to 92.7%, greater than or equal to 93%, greater than or equal to 94%, greater than or equal to 95%, greater than or equal to 96%, greater than or equal to 97%, greater than or equal to 98%, etc.

[0121] Specifically, the capacity retention rate of the battery 100 after 3000 cycles at 25°C may be, but is not limited to, greater than or equal to 93.4%, greater than or equal to 94%, greater than or equal to 95%, greater than or equal to 96%, greater than or equal to 97%, greater than or equal to 98%, etc.

[0122] Specifically, the capacity retention rate of the battery 100 stored at 45° C. for 30 days may be, but is not limited to, greater than or equal to 90.8%, greater than or equal to 92%, greater than or equal to 93%, greater than or equal to 94%, greater than or equal to 95%, greater than or equal to 96%, greater than or equal to 97%, greater than or equal to 98%, etc.

[0123] Specifically, the capacity retention rate of the battery 100 after 500 cycles at 80° C. may be, but is not limited to, greater than or equal to 82%, greater than or equal to 84%, greater than or equal to 86%, greater than or equal to 88%, greater than or equal to 90%, greater than or equal to 92%, etc.

[0124] According to tests, the battery 100 of the embodiment of the present application has a high cycle capacity retention rate at -40°C to 80°C, has a wide operating temperature range, and can better adapt to changes in ambient temperature.

[0125] The battery 100 and the electrolyte according to the embodiment of the present application are further described below through specific examples.

[0126] Example 1 to Example 29, Comparative Example 1 to Comparative Example 13

[0127] The preparation method of the battery 100 of each embodiment and comparative example includes:

[0128] (1) Preparation of positive electrode sheet 110: The positive electrode active material sodium iron phosphate, acetylene black (positive electrode conductive agent), and polyvinylidene fluoride (positive electrode binder) are dispersed in N-methylpyrrolidone (NMP) solvent at a mass ratio of 97:1:2, and mixed evenly to obtain positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector 111 aluminum foil, and after drying, cold pressing, slitting, and cutting, the positive electrode sheet 110 is obtained.

[0129] (2) Preparation of negative electrode sheet 130: artificial graphite, acetylene black (negative electrode conductive agent), styrene-butadiene rubber and sodium carboxymethyl cellulose, which are negative electrode active materials, are dispersed in deionized water at a mass ratio of 95:2:2:1 and mixed evenly to obtain negative electrode slurry. The negative electrode slurry is coated on the copper foil of the negative electrode collector 131. After drying, cold pressing, slitting and cutting, the negative electrode sheet 130 is obtained.

[0130] (3) Electrolyte preparation process: In an argon atmosphere glove box with a moisture content of less than or equal to 10 ppm, sodium hexafluorophosphate, sodium difluorophosphate and sodium bis(fluorosulfonyl)imide are dissolved in a mixed organic solvent consisting of a first organic solvent and a second organic solvent to prepare an electrolyte; wherein the molar concentration of sodium hexafluorophosphate in the electrolyte is 1.0 mol / L, the first organic solvent comprises ethylene carbonate and diethyl carbonate, and the mass ratio of the ethylene carbonate to the diethyl carbonate in the first organic solvent is 1:1. For the types and mass fractions of sodium hexafluorophosphate, sodium difluorophosphate, sodium bis(fluorosulfonyl)imide, the first organic solvent, the second organic solvent, etc., please refer to Table 1 below.

[0131] (4) Preparation of the separator 120 : A 16 μm polyethylene porous film was used as the separator 120 .

[0132] (5) Assembly of battery 100: The positive electrode sheet 110, the separator 120, and the negative electrode sheet 130 are stacked in sequence to form an electrode assembly. The electrode assembly is wound to obtain a bare cell. The middle area, top area, and bottom area of ​​the termination area (i.e., the end of the cell) are respectively adhered with termination tape. The cell is then placed in a polypropylene plastic outer packaging and injected with electrolyte. After vacuum packaging, standing, forming, shaping, and other processes, a soft-pack battery 100 is obtained.

[0133] Table 1 Composition of the electrolytes of the embodiments and comparative examples

[0134]

[0135]

[0136] The following performance tests were performed on the batteries 100 of the above embodiments and comparative examples:

[0137] (1) Discharge capacity retention rate at -40°C: The battery 100 after capacity conversion is charged and discharged for two cycles at 25°C / 0.5P, and the discharge capacity at 25°C is recorded. The battery 100 is then placed in a -40°C incubator and discharged at the same discharge power, and the discharge capacity is recorded. The ratio of the discharge capacity at -40°C to the discharge capacity at 25°C is calculated, which is the discharge capacity retention rate of the battery 100 at -40°C.

[0138] (2) Capacity retention rate after 200 cycles at -20°C: Battery 100 was subjected to a charge and discharge cycle test on a charge and discharge instrument (Nebula Charge and Discharge Test System - BAT-NEEFLCT-05300-V010), with the test temperature being -20°C, the cycle rate being 0.2C (i.e., both the charge rate and the discharge rate were 0.2C), the charging voltage being 1.5V to 3.5V, and the capacity retention rate after 200 cycles was calculated. The capacity retention rate of the cycle was calculated as follows: Capacity retention rate after the nth cycle = (discharge capacity after the nth cycle / discharge capacity of the first cycle) × 100%.

[0139] (3) Capacity retention after 200 cycles at 25°C: Battery 100 was subjected to a charge and discharge cycle test on a charge and discharge tester (Nebula Charge and Discharge Test System - BAT-NEEFLCT-05300-V010) at a test temperature of 25°C, a cycle rate of 1C (i.e., both the charge rate and the discharge rate were 1C), and a charging voltage of 1.5 V to 3.5 V. The capacity retention after 200 cycles was calculated.

[0140] (4) Capacity retention after 200 cycles at 80°C: Battery 100 was subjected to a charge and discharge cycle test on a charge and discharge tester (Nebula Charge and Discharge Test System - BAT-NEEFLCT-05300-V010) at a test temperature of 80°C, a cycle rate of 1C (i.e., both the charge rate and the discharge rate were 1C), and a charging voltage of 1.5 V to 3.5 V. The capacity retention after 200 cycles was calculated.

[0141] (5) Capacity retention rate of 5C rate discharge: Battery 100 was subjected to charge and discharge cycle test on a charge and discharge instrument (Nebula Charge and Discharge Test System - BAT-NEEFLCT-05300-V010). The test temperature was 25°C, the discharge rates were 1C, 2C, 3C, 4C, and 5C, the charge rate was 1C, and the charging voltage was 1.5V to 3.5V. The capacity retention rate of rate discharge was calculated as follows: 5C rate discharge capacity retention rate = (5C rate discharge capacity / 1C rate discharge capacity) × 100%.

[0142] (6) Capacity retention rate after storage at 45°C for 30 days (30D): The test temperature is 25°C, and the battery 100 is charged to 3.5V at a constant current of 0.5C, and then charged to 0.05C at a constant voltage. After standing for 10 minutes, it is discharged to 1.5V at 0.5C. The capacity obtained in this step is the initial discharge capacity C0. After standing for 10 minutes, the sodium ion battery 100 is charged to 3.5V at a constant current of 0.5C, and then charged to 0.05C at a constant voltage. After being stored in a 45°C oven for 30 days, it is recorded as the recovery capacity after three cycles of charge and discharge at a current of 0.5C. The residual capacity recovery rate is: the recovery capacity of the sodium ion battery 100 after placement / the initial discharge capacity C0×100%.

[0143] The test data of the battery 100 of the above embodiments and comparative examples are shown in Table 2 below.

[0144] Table 2 Test data of the battery 100 of each embodiment and comparative example

[0145]

[0146]

[0147] From the test results of Examples 1 to 5, Comparative Examples 1 and 2, it can be seen that when sodium difluorophosphate is not added to the electrolyte (Comparative Example 1), the discharge capacity retention rate of the battery 100 at -40°C, the cycle capacity retention rate at -20°C, the 5C discharge capacity retention rate, the cycle capacity retention rate at 25°C, the capacity retention rate after storage at 45°C for 30D, and the cycle capacity retention rate at 80°C are all low; when a certain amount of sodium difluorophosphate is added to the electrolyte, the discharge capacity retention rate at -40°C, the cycle capacity retention rate at -20°C, the 5C discharge capacity retention rate, the cycle capacity retention rate at 25°C, the capacity retention rate after storage at 45°C for 30D, and the cycle capacity retention rate at 80°C of the battery 100 are all increased. As the content of sodium difluorophosphate in the electrolyte increases, the discharge capacity retention rate at -40°C, the cycle capacity retention rate at -20°C, the 5C discharge capacity retention rate, the cycle capacity retention rate at 25°C, the 30D capacity retention rate stored at 45°C, and the 80°C cycle capacity retention rate of the battery 100 all show a trend of first gradually increasing and then gradually decreasing. When the content of sodium difluorophosphate not added to the electrolyte increases to a certain extent (such as in Comparative Example 2), the first additive cannot be completely dissolved.

[0148] In addition, from the test results of Examples 18 to 20 and Example 3, it can be seen that with the increase in the mass fraction of sodium difluorophosphate in the electrolyte, the discharge capacity retention rate at -40°C, the low-temperature cycle capacity retention rate, the 5C discharge capacity retention rate, the 45°C storage 30D capacity retention rate, and the 80°C cycle capacity retention rate of the battery 100 are all improved. When the mass fraction of sodium difluorophosphate increases to a certain extent, continuing to increase the mass fraction of sodium difluorophosphate has no significant effect on the performance of the battery 100. This is because the introduction of sodium difluorophosphate promotes the formation of an inorganic component-rich SEI interface film, inhibits the increase in impedance during the cycle of the battery 100 and the consumption of solvents and sodium salts, thereby improving the low-temperature, room-temperature and high-temperature cycle capacity retention rates of the battery 100.

[0149] From the test results of Example 3, Example 6 to Example 9, Comparative Example 3 and Comparative Example 4, it can be seen that when sodium bis(fluorosulfonyl)imide is not added to the electrolyte (Comparative Example 3), the discharge capacity retention rate of battery 100 at -40°C, the cycle capacity retention rate at -20°C, the 5C discharge capacity retention rate, the cycle capacity retention rate at 25°C, the capacity retention rate after storage at 45°C for 30D, and the cycle capacity retention rate at 80°C are all low; when a certain amount of sodium bis(fluorosulfonyl)imide is added to the electrolyte, the discharge capacity retention rate at -40°C, the cycle capacity retention rate at -20°C, the 5C discharge capacity retention rate, the cycle capacity retention rate at 25°C, the capacity retention rate after storage at 45°C for 30D, and the cycle capacity retention rate at 80°C of battery 100 are all increased. With the increase of the sodium bis(fluorosulfonyl)imide content in the electrolyte, the discharge capacity retention rate of battery 100 at -40°C, the cycle capacity retention rate at -20°C, the 5C discharge capacity retention rate, the cycle capacity retention rate at 25°C, the capacity retention rate after storage at 45°C for 30D, and the cycle capacity retention rate at 80°C all show a trend of first gradually increasing and then gradually decreasing.

[0150] In addition, from the test results of Examples 18 and 22, Examples 19 and 21, it can be seen that as the mass fraction of sodium bis(fluorosulfonyl)imide in the electrolyte increases, the conductivity of the electrolyte increases, and the rate performance and high and low temperature performance of the battery 100 are significantly improved. As the mass fraction of sodium bis(fluorosulfonyl)imide further increases, the viscosity of the electrolyte increases, and the discharge capacity rate and cycle capacity retention rate and rate performance of the battery 100 at low temperatures are reduced.

[0151] From the test results of Example 3, Example 10 to Example 13, Comparative Example 5 and Comparative Example 6, it can be seen that when the mass ratio of the first organic solvent to the second organic solvent in the electrolyte is too small (such as Comparative Example 6), the electrolyte is prone to stratification; with the increase of the mass ratio of the first organic solvent to the second organic solvent in the electrolyte, the discharge capacity retention rate of the battery 100 at -40°C, the cycle capacity retention rate at -20°C, the 5C discharge capacity retention rate, the cycle capacity retention rate at 25°C, the 45°C storage 30D capacity retention rate and the 80°C cycle capacity retention rate all first gradually increase and then gradually decrease.

[0152] From the test results of Example 3, Example 16 to Example 18, Comparative Example 12, and Comparative Example 13, it can be seen that, compared with Example 3 with only the first additive, the addition of fluoroethylene carbonate can better improve the high-temperature cycle capacity retention rate of the battery 100. In addition, as the content of fluoroethylene carbonate in the electrolyte increases, the -20°C (low temperature) cycle capacity retention rate of the battery 100 gradually decreases, the 25°C (normal temperature) cycle capacity protection rate remains basically unchanged, and the 80°C (high temperature) cycle capacity retention rate, when the content of fluoroethylene carbonate in the electrolyte increases to a certain extent, the battery 100 is prone to gassing.

[0153] From the test results of Example 18, Example 23 to Example 25, it can be seen that as the mass fraction of methylcyclopentane in the electrolyte increases, the low-temperature discharge capacity retention rate, cycle stability and rate performance of the battery 100 are improved, and the introduction of methylcyclopentane significantly reduces the viscosity and melting point of the electrolyte. When the mass fraction of methylcyclopentane exceeds 60%, the high and low temperature performance of the electrolyte is reduced, because the content of the high dielectric constant cyclic carbonate is too low, and methylcyclopentane does not have ion-conducting properties.

[0154] From the test results of Example 18, Example 26 and Example 27, it can be seen that compared with n-hexane and octane, methylcyclopentane has better high and low temperature performance, and the ring structure gives it greater steric hindrance and chemical stability, and the high and low temperature cycle stability is better than that of n-hexane and octane.

[0155] From the test results of Example 18, Example 28 and Example 29, it can be seen that compared with 1,3-propylene sultone and vinyl sulfate, the SEI interface film formed when the content of fluoroethylene carbonate is less than 2% is thinner, rich in inorganic components, and can inhibit the growth of impedance and electrolyte consumption during the cycle process, and has significant advantages in improving the storage and cycle performance of battery 100; however, the SEI interface film formed by the two types of additives, 1,3-propylene sultone and vinyl sulfate, has a large impedance, and the improvement in low-temperature performance is not as good as fluoroethylene carbonate.

[0156] It can be seen from Example 18 and Comparative Examples 7 to 11 that partially introducing or not introducing the first additive, the second additive, and the second solvent will deteriorate the high and low temperature performance and rate performance of the battery 100. The electrolyte without the introduction of methylcyclopentane cannot be discharged at -40°C, which is mainly because the viscosity of the electrolyte increases rapidly and the conductivity decreases sharply in the temperature range of -30°C to -20°C.

[0157] In summary, the embodiment of the present application not only can broaden the operating temperature window of the electrolyte, but also can effectively inhibit the interface reaction of the positive electrode plate 110 / electrolyte and the negative electrode plate 130 / electrolyte, thereby extending the service life of the battery 100 by adding a non-polar alkane as the second organic solvent and sodium difluorophosphate and sodium bis(fluorosulfonyl)imide as the first additive to the electrolyte with carbonate as the first organic solvent and sodium hexafluorophosphate as the sodium salt.

[0158] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.

[0159] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.

Claims

1. An electrolyte, characterized in that: The electrolyte includes an electrolyte salt, a first organic solvent, a second organic solvent, and a first additive, wherein the first organic solvent is a polar solvent, the second organic solvent is a non-polar solvent, and the first additive includes sodium difluorophosphate and sodium bis(fluorosulfonyl)imide.

2. The electrolyte according to claim 1, characterized in that The mass ratio a1 / a2 of the first organic solvent to the second organic solvent is in the range of 0.25≤a1 / a2≤3.

3. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass fraction a1 of the first organic solvent is in the range of 20wt%≤a1≤70wt%; the mass fraction a2 of the second organic solvent is in the range of 20wt%≤a2≤65wt%.

4. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass fraction b of the first additive is in the range of 1.2wt%≤b≤5.5wt%.

5. The electrolyte according to claim 4, characterized in that In the electrolyte, the mass ratio b1 / b2 of the mass fraction b1 of the sodium difluorophosphate to the mass fraction b2 of the sodium bis(fluorosulfonyl)imide is in the range of 0.075≤b1 / b2≤0.

35.

6. The electrolyte according to claim 4, characterized in that In the electrolyte, the mass fraction b1 of the sodium difluorophosphate is in the range of 0.2wt%≤b1≤0.8wt%.

7. The electrolyte according to claim 4, characterized in that In the electrolyte, the mass fraction b2 of the sodium bis(fluorosulfonyl)imide is in the range of 1wt%≤b2≤5wt%.

8. The electrolyte according to any one of claims 1 to 7, characterized in that: The first organic solvent includes alkanes, and the alkanes include at least one of n-hexane, octane and methylcyclopentane; the second organic solvent includes carbonate.

9. The electrolyte according to any one of claims 1 to 7, characterized in that: The electrolyte further includes a second additive, and the second additive includes at least one of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, 1,3-propene sultone, vinyl sulfate, and vinyl sulfite.

10. A battery, characterized in that: include: The electrolyte, positive electrode sheet, separator and negative electrode sheet as described in any one of claims 1 to 9.

11. The battery according to claim 10, characterized in that The battery satisfies at least one of the following conditions: The discharge capacity retention rate of the battery at -40°C is greater than or equal to 75.4%; The capacity retention rate of the battery after 200 cycles at -20°C is greater than or equal to 80.3%; The capacity retention rate of the battery at 25°C and 5C discharge rate is greater than or equal to 92.7%; The capacity retention rate of the battery after 3000 cycles at 25° C. is greater than or equal to 93.4%; The capacity retention rate of the battery stored at 45° C. for 30 days is greater than or equal to 90.8%; and The capacity retention rate of the battery after 500 cycles at 80° C. is greater than or equal to 82%.

12. An energy storage device, characterized in that: include: Box; as well as A plurality of batteries according to claim 10 or 11, wherein the plurality of batteries are housed in the casing.

13. An energy storage system, characterized in that: include: An electric energy conversion device and an energy storage device as described in claim 12, wherein the electric energy conversion device is electrically connected to the energy storage device, the electric energy conversion device is used to convert other forms of energy into electric energy, and the energy storage device is used to store the electric energy.